REVOLUTIONIZING HEALTHCARE: A REVIEW OF 3D PRINTING IN DENTISTRY AND DRUG DELIVERY - ABHILASHA WAGHADKAR; VIDYA LOHE; SUWARNA DANGORE; MANISHA WAGHADKAR; MUJIBULLAH SHEIKH (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Three-dimensional (3D) printing will revolutionize healthcare by allowing personalized, efficient, and decentralized healthcare solutions. This assessment synthesizes current knowledge on the objectives, support, and limitations of 3D printing in dentistry and medicine distribution. 3D printing makes it easier to manufacture surgical instruments, diagnostic models, crowns, bridges, and bioprinted soft tissues in dentistry. It enables personalized, on demand formulations, such as oral polypills and microneedle array, together with a tunable release profile for drug delivery. Although promising, the field still faces several challenges, including technical obstacles, limited mechanical longevity of dental polymers, scalability issues in bioprinting, insufficient safety data, and the lack of uniform standards. Critics of research on how emerging technologies, such as Al and green components, can overcome existing obstacles, focusing on proposing realistic plans for future integration of 3D printing into global healthcare systems. Examples, such as the high success rates for 3D dental implant production and the Food and Drug Administration-approved 3D-printed drug Spritam, demonstrate the potential of 3D printing. The review also highlights the techn